Visible up-conversion and near-infrared luminescence of Er3+/Yb3+ co-doped SbPO4-GeO2 glasses - Manzani, D. [UNESP] (2016)
Recent advances in glass chemistry have led to new multifunctional optical glasses of great technological importance. Glasses containing high amounts of antimony have been studied for use in nonlinear optics, near-infrared transmission, and as hosts for rare-earth ions in photonic devices. This work describes a luminescence study of Er3+ and Er3+/Yb3+ co-doping in a new SbPO4-GeO2 binary glass system. Near-infrared and visible up-conversion emissions were observed in the green and red regions, which are enhanced when the samples are co-doped with Yb3+. Near-infrared emissions have good quantum efficiency and full width half maximum of 61 nm. Visible up-conversion emissions are governed by two photons and described by excited state absorption, energy transfer and cross-relaxation processes.